(untitled) (Balneo and PRM Research Journal, 2024)
: A mathematical model is presented to determine the spatial displacement of an endeffector attached to the human upper limb kinematic chain. The proposed method in-volves the successive application of the homogenous rotation matrices associated with each element movement to determine the general transfer matrix or the so-called homoge-neous transformations matrix. This method is proven to be an error free method for esti-mating the position and orientation of an end-effector attached to a kinematic chain. The methodology presented in this paper combines a well know mathematical technique used in engineering (in the development of space robots) and the anatomical features of the human upper limb to estimate not only the end-effector 3D position but also the limb pos-es during a particular displacement. Keywords: homogenous transformation, mathematical model, human body, kinematic